به‌ڕێوه‌بردنی فشاره‌ ده‌روونیه‌كان و په‌یوه‌ندی به‌ ووشیاری ئه‌منی لای ئه‌فسه‌رانی هێزه‌كانی ئاسایش له‌ شاری سلێمانی - خالد, حسن فخرالدین; الدین, یاسین سمیع نجم (Sulaimani Journal for Humanities, 2022)
The objectives of this research is to know the level of psychological stress management and security awareness among Asayish forces officers of Sulaymaniyah Governorate, and to know the relation between psychological stress management and security awareness among Asayish forces officers of Sulaymaniyah governorate, and to find a statistical difference for the level of psychological stress management and security awareness among officers of the Sulaymaniyah Asayish forces according to military ranking variable (Captain, Major, Lieutenant colonel, Colonel and Brigadier general). In order to achieve these objectives, the researcher used a descriptive method. The research tools consisted of two psychological scales, (management of psychological stress) scale were consisted of (45) questionnaire items. The Second scale (security awareness), the researcher depended on (A'oula, 2015) scale which was consisted from (78) questionnaire items. To verify the terms of the psychometric scales, the researcher made a statistical analysis for the scale's questionnaire items. The research sample consisted of all officers of Asayish forces (Asayish directorate of Sulaimaniyah governorate) from both genders (male, female) who are serving continuously till (2021) year. The researcher has used (SPSS) program in order to analyse the data and the information collected from the research samples.As the result of data analysis of the research outcomes, The researcher concluded : The ability to manage psychological stress among the officers of the Asayish forces of Sulaymaniyah governorate, in general is at a high level. The level of security awareness among officers of the Asayish forces of Sulaimaniyah governorate, in general is at a high level. There was evidence of a statistical difference in the level of psychological stress management and security awareness among the Asayish forces of the Sulaymaniyah governorate, according to the military ranking variable, which was classified into five military ranks (Captain, Major, Lieutenant colonel, Colonel and Brigadier general). The relation between psychological stress management and security awareness among Asayish forces officers of Sulaymaniyah governorate, it was a positive parallel correlation. At the end of the research, the researcher presented some recommendations and suggestions.